Broadening the Lean Six Sigma concept through employee adaptability: a literature review. (5th November 2019) - Sony, Michael; Mekoth, Nandakumar
LSS is one of the most widely implemented initiatives within the organisations. Employees are one of the most important factors for its success. However, due to the absence of an implementation framework, it creates a complex environment for the employees. The purpose of this paper is to examine the different dimensions an employee must adapt while implementing LSS. An integrative literature review is carried for the last 25 years. This research paper finds eight dimensions on which employee has to adapt while implementing LSS. The eight dimensions along with research propositions for future research are discussed. There are many studies on the implementation aspect of LSS. There is yet to be a study discussing how an employee would adapt to LSS initiatives for a sustainable implementation. This is the first literature review carried out on employee adaptability and LSS. This study will add value to organisations so that they can better recruit and manage their employees. Likewise, the academicians will also benefit from the literature review and research propositions for the future research agenda.